A Study of Corneal Biomechanics in Delayed-Onset Mustard Gas Keratopathy Compared to Cases With Corneal Scarring and Normal Corneas. Issue 2 (March 2019) - Jadidi, Khosrow; Mohazzab-Torabi, Saman; Pirhadi, Shiva; Naderi, Mostafa; Yekta, Abbasali; Sardari, Sara; Khabazkhoob, Mehdi
Abstract : Purpose: This study compares the corneal biomechanical properties, as measured with Corvis ST, in three groups of cases with delayed-onset mustard gas keratopathy (DMGK), chronic corneal scarring (CCS), and those with normal corneas. Methods: Forty-five eyes were enrolled in the DMGK, CCS, and normal groups (15 eyes each). All patients were examined with the slitlamp and Corvis ST. Extracted corneal biomechanical parameters included first and second applanation time (AT1, AT2), first and second applanation length (AL1, AL2), first and second applanation velocity (AV1, AV2), deformation amplitude (DA), highest concavity time, peak distance, highest concavity radius (HCR), central corneal thickness, corrected intraocular pressure (IOP), and noncorrected IOP. Results: The mean age of the participants in the DMGK, CCS, and normal groups was 49.20±5.16, 60.40±22.92, and 44.60±8.32 years, respectively. Comparison between DMGK and CCS groups showed significant differences in AT1, AT2, corrected IOP, and noncorrected IOP. There were also significant differences in AT1, AT2, HCR, DA, and noncorrected IOP between the DMGK and normal groups. None of the parameters were significantly different between the CCS and normal groups. Conclusion: There seems to be reduced corneal rigidity and stiffness in cases exposed to mustard gas, which causes the cornea in the DMGK group to become applanated more easily and take longer to rebound compared with the other two groups. Also, IOP was lower than normal in the DMGK group, and thus, misdiagnosis of glaucoma is likely for these patients.